2013
DOI: 10.1186/1757-4749-5-16
|View full text |Cite
|
Sign up to set email alerts
|

Secreted Listeria adhesion protein (Lap) influences Lap-mediated Listeria monocytogenes paracellular translocation through epithelial barrier

Abstract: BackgroundListeria adhesion protein (Lap), an alcohol acetaldehyde dehydrogenase (lmo1634) promotes bacterial paracellular translocation through epithelial cell junctions during gastrointestinal phase of infection. Secreted Lap is critical for pathogenesis and is mediated by SecA2 system; however, if strain dependent variation in Lap secretion would affect L. monocytogenes paracellular translocation through epithelial barrier is unknown.MethodsAmounts of Lap secretion were examined in clinical isolates of L. m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 21 publications
1
28
0
Order By: Relevance
“…It has already been shown that anaerobic pre-culture of Listeria monocytogenes enhances adhesion in in vitro cell culture assays and virulence in vivo in the guinea pig model (Bo Andersen et al, 2007). Anaerobic induction of InlB (inlB, lmo0433, log 2 RTL 1.3), involved in adherence to (Lindén et al, 2008) and invasion in (Pentecost et al, 2010) intestinal tissue, and LAP (a bifunctional enzyme, also with metabolic capability, lmo1634, described previously in the text as adh, log 2 RTL 1.4), involved in adherence (Burkholder et al, 2009) and paracellular translocation (Burkholder & Bhunia, 2010;Kim & Bhunia, 2013), was already described previously (Burkholder et al, 2009;Stritzker et al, 2004Stritzker et al, , 2005. In addition, we observed anaerobically an upregulation of lmo0971-lmo0973, encoding the Dlt proteins involved in Dalanine esterification of lipoteichoic acid and wall teichoic acid (dltD, dltC and dltB, log 2 1.2, 1.3 and 1.5).…”
Section: Anaerobiosis Triggers Virulence Gene Expression In Listeria mentioning
confidence: 99%
“…It has already been shown that anaerobic pre-culture of Listeria monocytogenes enhances adhesion in in vitro cell culture assays and virulence in vivo in the guinea pig model (Bo Andersen et al, 2007). Anaerobic induction of InlB (inlB, lmo0433, log 2 RTL 1.3), involved in adherence to (Lindén et al, 2008) and invasion in (Pentecost et al, 2010) intestinal tissue, and LAP (a bifunctional enzyme, also with metabolic capability, lmo1634, described previously in the text as adh, log 2 RTL 1.4), involved in adherence (Burkholder et al, 2009) and paracellular translocation (Burkholder & Bhunia, 2010;Kim & Bhunia, 2013), was already described previously (Burkholder et al, 2009;Stritzker et al, 2004Stritzker et al, , 2005. In addition, we observed anaerobically an upregulation of lmo0971-lmo0973, encoding the Dlt proteins involved in Dalanine esterification of lipoteichoic acid and wall teichoic acid (dltD, dltC and dltB, log 2 1.2, 1.3 and 1.5).…”
Section: Anaerobiosis Triggers Virulence Gene Expression In Listeria mentioning
confidence: 99%
“…In our previous study, it was demonstrated that three L. monocytogenes strains (i.e., H4, F4244, and F4262) of serotype 4b express various levels of LAP and exhibit variable adhesion and pathogenesis in a cell culture model (49). In the present study, these strains also generated differentiating scatter patterns on both BHIA and LBA media.…”
Section: Discussionmentioning
confidence: 61%
“…Western blotting and ELISA confirmed the high LAP production of the H4 strain (Fig. 8d) (49). This variation in the amount of protein synthesis may be one of the factors that contributed to the differences observed in the scatter patterns of the serotype 4b strains.…”
Section: Lap Expression Affects the Scatter Patterns Of L Monocytogementioning
confidence: 71%
See 1 more Smart Citation
“…These proteins were mostly cytosolic proteins previously documented as ‘moonlighting’ proteins (Henderson and Martin, ). Among these, we identified metabolic enzymes that do not have a typical signal peptide and proteins lacking a cell wall anchoring motif: pyruvate dehydrogenase (Lmo1053); 6‐phosphogluconate dehydrogenase (Lmo1376); alcohol‐acetaldehyde dehydrogenase (Lmo1634), also known as Lap for Listeria adhesion protein (Kim and Bhunia, ); glucose‐6‐phosphate isomerase (Lmo2367); triose phosphate isomerase (Lmo2457); a putative phosphoglycerate kinase (Lmo2458); and, fructose‐1,6‐bisphosphate aldolase (Lmo2556) (Table ). Some of these enzymes have been proposed to have more than one biological function in other pathogens, including virulence implications (Henderson and Martin, ; Henderson, ).…”
Section: Resultsmentioning
confidence: 99%